Phase transformations during the zeolitization of fly ashes - Monzón, Jorge Daniel (2017)
The reactivity of a fly ash discarded from a thermoelectric power station was evaluated in terms of its hydrothermal conversion into NaA-containing products. The influence of ash pretreatments and the effect of changes in the synthesis mixture composition on the evolution of the solid phase toward its conversion into zeolitic materials were studied. Activation by milling was not as effective as alkaline fusion. The highest levels of fly ash reactivity were obtained by applying an alkaline fusion treatment using sodium carbonate at 800 °C. It was observed that this particular ash activation induces a solid reordering that generates crystalline materials identified as NaAlSiO2 polymorphs that in turn are easily transformed into zeolite structures. Synthesis conditions for ash zeolitization as high as 60% were established.